1995
DOI: 10.1074/jbc.270.38.22577
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Hepatic Control Region of the Human Apolipoprotein E/C-I Gene Locus

Abstract: The specificity of expression in the liver of the human apolipoprotein (apo) E/C-I gene locus is determined by a hepatic control region (HCR) that is located 15 kilobases downstream of the apoE gene. DNase I footprint studies of this sequence using nuclear extracts identified a region of the HCR that is enriched in nuclear proteinbinding sites. Nuclease analysis of chromatin revealed liver-specific DNase I-hypersensitive sites that were associated with this region, and additional liver-specific nuclease-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 51 publications
3
62
0
3
Order By: Relevance
“…This 580-nucleotide region or a minimum of 319-nucleotide region containing the first three footprints are sufficient to direct hepatic expression of the apoE gene in transgenic mice (14). The present study showed that this 319-base pair region enhanced 2.5-fold the strength of the Ϫ545/ϩ18 apoC-II promoter in HepG2 cells and had no effect in CaCo-2 or COS-1 cells in the absence of HNF-4.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…This 580-nucleotide region or a minimum of 319-nucleotide region containing the first three footprints are sufficient to direct hepatic expression of the apoE gene in transgenic mice (14). The present study showed that this 319-base pair region enhanced 2.5-fold the strength of the Ϫ545/ϩ18 apoC-II promoter in HepG2 cells and had no effect in CaCo-2 or COS-1 cells in the absence of HNF-4.…”
Section: Discussionmentioning
confidence: 60%
“…an HRE which may bind different members of the hormone receptor family including HNF-4 (14). To test whether the HREs present in the proximal promoter and/or the HCR-1 contribute to the HNF-4 mediated transcriptional enhancement, we performed co-transfection experiments using the reporter construct HCR-1/(Ϫ545/ϩ18)CII CAT and HNF-4 expression plasmid.…”
Section: Hnf-4 Transactivates the Apoc-ii Promoter And The Apoc-ii Prmentioning
confidence: 99%
See 2 more Smart Citations
“…The LTR was also inserted at a distance (see "Experimental Procedures") in constructs with the apoC-I promoter where the LTR was removed, to test for the possibility that the LTR acts as an enhancer of the native promoter. The expression in liver is completely dependent on a distal HCR (27), and we saw no promoter activity of the apoC-I constructs without the presence of this HCR. The results of the transfections of HepG2 (liver) cells with a variety of apoC-I constructs are shown in Fig.…”
Section: Significance Of the Herv-e Ltrs In Expression Of Apoc-i And mentioning
confidence: 89%